`Irfani Sebagai Paradigma Etika Kritis Dalam Politik Islam - Sutikno, Sutikno (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2020)
This study focuses to reconstruction of political ethics which `Irfani paradigm as critical ethics in Islamic politics. Relevance of `Irfani as paradigm of critical ethics based on advcance of capitalism dan neoliberalism both politics and economics which arises moral and ethical changes for muslim politicians both in governnment and power structures. This study of ethics paradigm reconstruction was library research methods and uses socio-philosophical perspectives. Results of this study that urgency of `Irfani paradigm as an alternative solution. In `Irfani paradigm as critical ethics in Islam had deconstruction methods on objective and subjective reason and consciousness structures pragmatically and instrumentally. That paradigma made foundations of philosophy-sufism tradition in Islam which transformed in to contemporary political life. The `Irfani paradigma contribution as critical ethics in Islam leads to reconstruction from the instrumental rationality towards trancendental rationality through reconfirmation and reafirmation about meaning of politics and democracy and how to echieve in its orientation. The agenda of deconstruction above automatically arises that politics and democracy was not an area of achievement for egoistic and individualistic interests but an area of moral and ethical accountabilities for societal wellfareness.